Empathy and systemizing in preschool children - Janković-Nikolić, Marina (Specijalna edukacija i rehabilitacija, 2020)
Introduction. The Empathizing–Systemizing theory sees empathy and systemizing as two independent dimensions, which can be used for classification into five cognitive profiles or “brain types”. Objective. The aim of this research was to determine the relationship between empathy and systemizing in preschool children, and to determine gender differences in these abilities and brain types. Method. The sample consisted of 71 children from 5/6 to 7 years of age. Children’s versions of the Empathy Quotient – EQ-C and Systemizing Quotient - SQ-C (Auyeung et al., 2009) were used to assess empathy and systemizing. Results. According to our results, empathy and systemizing were moderately correlated: participants with higher empathy quotient also had a higher systemizing quotient. There were no gender differences in the assessed abilities. The only exception is the difference in the score calculated by subtracting systemizing and empathy quotient. On average, girls had the empathy quotient higher than the systemizing quotient, while boys showed the opposite pattern. There were no gender differences in the distribution of cognitive profiles (“brain types”) based on the aforementioned difference between systemizing and empathy. Conclusion. The results of this study may be used as baseline for comparison in future studies that would examine typically and atypically developing children.